Assessing marine mammal diversity in remote Indian Ocean regions, using an acoustic glider. (December 2022) - Torterotot, Maëlle; Béesau, Julie; Perrier de la Bathie, Cécile; Samaran, Flore
Abstract: Many observations collected from whaling logbooks or more recent satellite tags and acoustic surveys report that the Indian Ocean is a very important place for large baleen whales. They undergo long seasonal migrations from Southern feeding grounds to tropical and subtropical mating and breeding grounds. However, whether and where they stop to rest or feed during their long travels are poorly known. The Indian Ocean is also home to many odontocete species such as sperm whales, killer whales and multiple delphinid species. In this paper, we analyze passive acoustic data collected by an electric glider around two steep bathymetric features located in the Western sub-tropical Indian Ocean (Walters Shoal) and in the mid sub-tropical Indian Ocean (St. Paul and Amsterdam islands), both included in Important Marine Mammal Areas (IMMAs). The acoustic data were manually reviewed and annotated by two analysts. The aim of this experiment was to improve the knowledge on marine mammal presence in these little studied IMMAs. We found that bioacoustic activity was quite high in both monitored areas with 40% of the records containing marine mammal sounds in Walters Shoal and 70% in St. Paul and Amsterdam islands. Calls from Antarctic blue whales, Southwestern and Southeastern Indian Ocean pygmy blue whales, fin whales and an unidentified baleen whale were detected at one or both sites. Odontocete clicks and whistles were also recorded at both sites. The discussion puts these marine mammal acoustic detections back into the context of their seasonal and geographical presence already described by other studies in the Indian Ocean and makes hypotheses about the role of the two studied areas for marine mammals.